(3ShSjhdhLjG GdJTQjYGJ h GdEYdGe GdCefj (B/s - (3YOdj, YUeJ s ((3GdEScfOQjI (B:s (3OGQ GdeYQaI GdLGeYjI ,s, 2003)
(3JLO aj GdcJGH hSGFd GdEYdGe h eQGMdgG GdeNJdaI aj eUQ (B((3GdUMGaI(B- (3GdEPGYI (B- (3GdSjfeG(B- (3GdJdjaRjhf GdeG aj GdaUd GdKGfj JWhQ GdbhGfjf h GdJTQjYGJ GdefXeI ddUMGaI aj eUQ GdaUd GdKGdK jJMOK Yf MQjI GdUMGaI h Mb GdeDda GdQbGHI GdeUfaGJ GdafjI GdaUd GdQGHY GdbhGfjf h GdJTQjYGJ GdefXeI ddEPGYI h GddjaRjhf GdaUd GdNGeS GdEYdGe GdCefj aj eUQ adSaJg GSJQGJjLjJg aYGdjJgs
(3HHdjhZQGajG (B: (3U(B.271-274s
Keywords: (3GdEYdGe GdCefjs; (3GdJTQjYs; (3GdEYdGes; (3hSGFd GdEYdGe s